Top secret smackdown - Barnett, Mac (Barnett, Mac. Mac B., kid spy, 2019)
There is a legend that if the ravens at the Tower of London ever leave then Britain will fall, so when somebody steals the birds, the Queen calls for Mac B. to find the thief and retrieve them--a mission that takes him to Iceland, where he encounters secret submarines, hungry polar bears, and his arch-nemesis from the KGB.